Perancangan Sistem Aplikasi Layanan Penilaian Buku Pendidikan Agama Berbasis Web - Asep Taufik Muharram; Asep Erlan Maulana (Applied Information System and Management (AISM), 2019)
Religious Education Book Assessment Service activities are held by involving all stakeholders and other units. However, given the size and breadth of the scope and the limited manpower, budget and resources in carrying out these activities. So to overcome this problem, it is necessary to design a web-based system application that can serve quickly and be accessed 24 hours without limitation of space and time. The purpose of this study is to design a web-based application of the Religious Education Book Assessment Service. This application was created using the System Development Life Cycle (SDLC) development method with a waterfall model process and the system design was implemented with the Unified Modeling Language (UML). The result of this research is an application that can solve the problem of the implementation of the Religious Education Book Service activities that have been done conventionally.